2016
DOI: 10.1007/s00253-016-7481-0
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic evolution of yeast interspecies hybrids during high-sugar fermentation

Abstract: The yeasts of the Saccharomyces genus exhibit a low pre-zygotic barrier and readily form interspecies hybrids. Following the hybridization event, the parental genomes undergo gross chromosomal rearrangements and genome modifications that may markedly influence the metabolic activity of descendants. In the present study, two artificially constructed hybrid yeasts (Saccharomyces cerevisiae x Saccharomyces uvarum and S. cerevisiae x Saccharomyces kudriavzevii) were used in order to evaluate the influence of high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…This was the case for example with S. cerevisiae × S. uvarum hybrids, where the S. uvarum moiety was gradually reduced after successive meiotic (Antunovics et al 2005) or mitotic (Masneuf-Pomarède 2007; Sebastiani et al 2002) divisions. Likewise, Lopandic et al (2016) noted the loss of S. kudriavzevii chromosomes from an artificial S. cerevisiae × S. kudriavzevii hybrid, particularly after these fertile hybrids underwent meiosis. A similar reduction in S. kudriavzevii DNA has been observed in natural wine and beer hybrids (González et al 2008; Peris et al 2012).…”
Section: Hybrid Genome Function and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This was the case for example with S. cerevisiae × S. uvarum hybrids, where the S. uvarum moiety was gradually reduced after successive meiotic (Antunovics et al 2005) or mitotic (Masneuf-Pomarède 2007; Sebastiani et al 2002) divisions. Likewise, Lopandic et al (2016) noted the loss of S. kudriavzevii chromosomes from an artificial S. cerevisiae × S. kudriavzevii hybrid, particularly after these fertile hybrids underwent meiosis. A similar reduction in S. kudriavzevii DNA has been observed in natural wine and beer hybrids (González et al 2008; Peris et al 2012).…”
Section: Hybrid Genome Function and Stabilitymentioning
confidence: 99%
“…However, recent studies on the use of de novo S. cerevisiae interspecific hybrids with S. kudriavzevii (Bellon et al 2011; Lopandic et al 2016), S. mikatae (Bellon et al 2013), S. paradoxus (Bellon et al 2011), and S. uvarum (Bellon et al 2015; Lopandic et al 2016) for wine making have revealed the potential for increasing aromatic diversity and fermentation performance. As many of these “alternative” Saccharomyces species are also cold-tolerant, e.g., S. kudriavzevii and S. uvarum (Gonçalves et al 2011; López-Malo et al 2013; Paget et al 2014), they represent feasible alternatives to S. eubayanus in interspecific hybrids for lager brewing purposes and may compensate for the current paucity of S. eubayanus isolates.…”
Section: Artificial Hybridsmentioning
confidence: 99%
“…Examples of the latter are the chromosome III from S. cerevisiae that has high loss frequency [28] and the chromosome XII from S. bayanus being partially incompatible with the S. cerevisiae genome [30]. This phenomenon seems to be strain and species specific [28, 32]. S. cerevisiae  ×  S. uvarum and S. cerevisiae  ×  S. kudriavzevii hybrids show different rates of chromosome loss with hybrids involving S. kudriavzevii being more unstable [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cold tolerance seems the main phenotypic contribution of S. eubayanus to the natural and artificial lager yeast strains [22, 25, 37], but the presence of an additional high-affinity fructose transporter, Fsy1, could provide hybrids with improved ability to reduce the critical accumulation of fructose in the later phases of the wine and cider fermentations [32]. Fructose represents the larger portion of fermentable sugars in apple juice, being usually present in concentration two times higher than glucose [56].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of our approach is that it allows quantification of respiration and growth on 95 substrates simultaneously, providing within-experiment controls and comparisons that are not subject to variation introduced in a lower-throughput framework (Atanasova et al, 2010; Druzhinina et al, 2010; Blumenstein et al, 2015a,b). PMs have been used in diverse studies involving bacteria (reviewed in Bochner, 2008), and since their development have been extended to work with fungi, including yeasts and filamentous strains (reviewed in Bochner, 2003; Druzhinina et al, 2006; Atanasova and Druzhinina, 2010; Pfliegler et al, 2014). To our knowledge, PMs have not been used previously to explore interactions among microbes or more specifically, the effects of bacterial endosymbionts on fungal phenotypes.…”
Section: Introductionmentioning
confidence: 99%